2015
DOI: 10.1093/jxb/erv445
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors WRKY70 and WRKY11 served as regulators in rhizobacteriumBacillus cereusAR156-induced systemic resistance toPseudomonas syringaepv.tomatoDC3000 in Arabidopsis

Abstract: The activation of both the SA and JA/ETsignalling pathways may lead to more efficient general and broad resistance to Pst DC3000 by non-pathogenic rhizobacteria. However, the mechanisms that govern this simultaneous activation are unclear. Using Arabidopsis as a model system, two transcription factors, WRKY11 and WRKY70, were identified as important regulators involved in Induced Systemic Resistance (ISR) triggered by Bacillus cereus AR156. The results revealed that AR156 treatment significantly stimulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 84 publications
2
70
0
Order By: Relevance
“…Indeed, the study of Guo & Stotz (2007) has also concluded that defence against S. sclerotiorum in Arabidopsis is dependent on SA and ET/ JA signalling. According to Jiang et al (2016), the simultaneous activation of the SA-and ET/JA-signalling pathways is modulated via WRKY11 and WRKY70 and leads to an additive effect on the level of induced protection. It is tempting to speculate that the highly protective activity of K165 against S. sclerotiorum probably lies in the additive effect of the simultaneous activation of the SA-and ET/JA-dependent defences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the study of Guo & Stotz (2007) has also concluded that defence against S. sclerotiorum in Arabidopsis is dependent on SA and ET/ JA signalling. According to Jiang et al (2016), the simultaneous activation of the SA-and ET/JA-signalling pathways is modulated via WRKY11 and WRKY70 and leads to an additive effect on the level of induced protection. It is tempting to speculate that the highly protective activity of K165 against S. sclerotiorum probably lies in the additive effect of the simultaneous activation of the SA-and ET/JA-dependent defences.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR-mediated induced systemic resistance (ISR) has been demonstrated against fungi, bacteria, and viruses in Arabidopsis (Arabidopsis thaliana), bean (Phaseolus vulgaris), and tomato (Solanum lycopersicum) under conditions in which the inducing bacteria and the challenging pathogens remained spatially separated . ISR induced by PGPR is phenotypically similar to pathogen-induced systemic acquired resistance (SAR) (Jiang et al, 2015;Van der Ent et al, 2008;Van Loon et al, 1998). Whereas SAR depends on the salicylic acid (SA) pathway, which is followed by pathogenesis-related (PR) gene expression, such as PR1, PR2, and PR5 (Jiang et al, 2016(Jiang et al, , 2015, ISR depends both on the jasmonic acid (JA), and ethylene (ET) pathways (Jiang et al, 2015;Van Loon et al, 1998) and is combined with the accumulation of phytoalexins and formation of physical barriers such as callose and lignin (Jiang et al, 2015;Van Oosten et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such type of ISR was also documented in Arabidopsis thaliana triggered by the plant growth‐promoting rhizobacterium Bacillus cereus AR156 (Niu et al ., ). In AR156‐triggered ISR, the activating JA‐signalling pathway was achieved by downregulating the transcription factor WRKY11 and activating SA‐signalling pathway by upregulating WRKY70 (Jiang et al ., ). Based on our findings, it can be speculated that GJ‐22 may produce unique microbe‐associated molecular patterns (MAMPs) recognized by N. benthamiana, leading to the generation of this distinct ISR.…”
Section: Discussionmentioning
confidence: 97%